Alkestis - Euripides,Walton, J. Michael (Bloomsbury, 2013)
When Apollo was exiled for nine years from his Olympian home, he found shelter and hospitality at the palace of King Admetus. To pay him back, Apollo offers Admetus the chance to live beyond the day that fate has decided he will die. There is only one catch: when death comes to get him, Admetus must find a willing substitute. Having been rebuffed by his aging (but not ailing) father, Admetus finds a willing proxy in his wife, the eponymous Alkestis, who is brought to Death's door, indeed is led through it, only to be rescued by Admetus's old friend Herakles, who wrestles with Death, and wins.
10.5040/9781472503756.00000031
Keywords: Drama; Alcestis (Greek mythology)